Evolutionary dynamics of the plastid inverted repeat: the effects of expansion, contraction, and loss on substitution rates - Andan Zhu; Wenhu Guo; Sakshi Gupta; Weishu Fan; Jeffrey P. Mower (2015)
Rates of nucleotide substitution were previously shown to be several times slower in the plastid inverted repeat (IR) compared with single-copy (SC) regions, suggesting that the IR provides enhanced copy-correction activity. To examine the generality of this synonymous rate dependence on the IR, we compared plastomes from 69 pairs of closely related species representing 52 families of angiosperms, gymnosperms, and ferns. We explored the breadth of IR boundary shifts in land plants and demonstrate that synonymous substitution rates are, on average, 3.7 times slower in IR genes than in SC genes. In addition, genes moved from the SC into the IR exhibit lower synonymous rates consistent with other IR genes, while genes moved from the IR into the SC exhibit higher rates consistent with other SC genes. Surprisingly, however, several plastid genes from Pelargonium, Plantago, and Silene have highly accelerated synonymous rates despite their IR localization. Together, these results provide strong evidence that the duplicative nature of the IR reduces the substitution rate within this region. The anomalously fast-evolving genes in Pelargonium, Plantago, and Silene indicate localized hypermutation, potentially induced by a higher level of error-prone double-strand break repair in these regions, which generates substitutional rate variation.